Co-hydrothermal carbonization of corn stover and food waste: Characterization of hydrochar, synergistic effects, and combustion characteristic analysis. Issue 6 (December 2022) - Wang, Qing; Wu, Shuang; Cui, Da; Pan, Shuo; Xu, Fang; Xu, Faxing; Wang, Zhenye; Li, Guozhong
Abstract: Hydrochar was prepared via the co-hydrothermal carbonization (Co-HTC) method using corn stover (CS) and food waste (FW) as materials, and the influences of the synergistic effect of Co-HTC on fuel performances and combustion behavior were analyzed. Characterization of hydrochar was conducted using elemental analysis, industrial analysis, SEM, BET, XRD, and FTIR. The outcomes indicated that the higher heating values (HHVs) of hydrochar increased, the atomic ratios of H/C and O/C decreased, the fuel ratios ranged from 0.33 to 0.57, and the average pore diameter decreased when the FW ratio was increased. The synergistic effect of Co-HTC of CS and FW improved hydrochar yield, energy yield, organics retention, and C capture efficiency. Thermogravimetric and kinetic analysis showed that Co-HTC improves the combustion characteristics of hydrochar. Thus, production of hydrochar via Co-HTC of CS and FW provides some guidance for the resourcing and reducing solid organic waste, and offers a promising direction for renewable energy production. Highlights: Co-hydrothermal carbonization (Co-HTC) of corn stover and food waste was discovered. The synergistic mechanism of Co-HTC of corn stover and food waste was proposed. The synergistic effect of Co-HTC improved hydrochar quality and combustion performance This work provides a favorable basis for the feasibility of preparing hydrochar as fuel via Co-HTC of organic solid wastes.